COVID-19 associates with semen inflammation and sperm quality impairment that reverses in the short term after disease recovery - Martinez, María Sol; Ferreyra, Fernando Nicolás; Paira, Daniela Andrea; Rivero, Virginia Elena; Olmedo, José Javier; Tissera, Andrea Daniela; Molina, Rosa Isabel; Motrich, Rubén Darío (Frontiers in Physiology, 2023)
COVID-19 exerts deleterious effects on the respiratory, cardiovascular, gastrointestinal, and central nervous systems, causing more severe disease in men than in women. However, cumulative reported data about the putative consequences on the male reproductive tract and fertility are controversial. Furthermore, the long-term effects of SARS-CoV-2 infection are still uncertain. In this study, we prospectively evaluated levels of inflammatory cytokines and leukocytes in semen and sperm quality parameters in a cohort of 231 reproductive-aged male patients, unvaccinated, who had recovered from mild or severe COVID-19 and in 62 healthy control individuals. Sperm quality was assessed early (less than 3 months) and long (more than 3 and up to 6 months) after having COVID-19. Interestingly, and unlike most reported studies, available extensive background and baseline data on patients' sperm quality allowed performing a more accurate analysis of COVID-19 effects on sperm quality. Significantly higher levels of IL-1β, TNF and IFNγ were detected in semen from patients recently recovered from mild and/or severe COVID-19 with respect to control individuals indicating semen inflammation. Moreover, patients recovered from mild and/or severe COVID-19 showed significantly reduced semen volume, lower total sperm counts, and impaired sperm motility and viability. Interestingly, all observed alterations returned to baseline values after 3 or more months after disease recovery. These results indicate that COVID-19 associates with semen inflammation and impaired semen quality early after disease. However, long COVID-19 seems not to include longterm detrimental consequences on male fertility potential since the observed alterations were reversible after 1-23 spermatogenesis cycles. These data constitute compelling evidence allowing a better understanding of COVID-19 associated sequelae, fundamental for semen collection in assisted reproduction.